Manajemen Kurikulum Integratif Berbasis Multi-Kurikulum di Pesantren - Karomah Yuliana Putri Yuliana Putri; Oki Dermawan; Aditia Fradito (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
This study aims to analyze the management of an integrative curriculum at Pondok Pesantren Darul Falah Bandar Lampung, which combines the Salafiyyah Curriculum, KMI Gontor Curriculum, and the Ministry of Religious Affairs Curriculum into a unified educational system. The research employs a qualitative approach with a case study design, where data were collected through in-depth interviews, participatory observation, and document analysis, and then analyzed interactively through data reduction, data display, and conclusion drawing. The findings indicate that at the planning stage, curriculum integration remains partial and is not yet supported by a comprehensive conceptual design. At the implementation stage, the curriculum has been applied simultaneously within a boarding school system; however, it results in a high learning burden and suboptimal synchronization of learning materials. Meanwhile, at the evaluation stage, assessment systems are still conducted separately, thus failing to measure learning outcomes holistically. These findings highlight that the success of an integrative curriculum is strongly determined by the systemic coherence of curriculum management functions, including planning, implementation, and evaluation. The implications of this study suggest the need to develop a structured integrative curriculum management model through strengthening coordination among stakeholders, organizing a proportional learning load, and developing an integrated evaluation system to enhance the quality of Islamic boarding school education sustainably.